Influence of cryogenic treatment on the metallurgy of ferrous alloys: A review. Issue 16 (10th December 2017) - Kumar, T. Vignesh; Thirumurugan, Rama; Viswanath, B.
ABSTRACT: The research area "Cryogenic Treatment of Materials" has been the subject of a multitude of research studies and therefore needs a proper review article to highlight the present state of understanding and to define the future research direction. Though reviews on cryogenic processing of tool steels are available, there has not been a review that attempts to systematically discourse the effect of cryogenic treatment on the metallurgy of various ferrous alloys. While previous reviews address transformation of retained austenite and the formation of fine precipitated carbides as the major phenomena of cryogenic treatment, developments such as the refinement of pearlite matrix, formation of fine martensite, and enhancement of properties in low carbon steel and cast iron are discussed in detail in this article. In addition, the influence of individual treatment parameters, their sequence, and the effect of room temperature stabilization on the metallurgical changes are extensively addressed. Moreover, many of the contradicting observations/conclusions such as detwinning of martensite and dissolution of secondary carbides during cryogenic treatment are highlighted for further clarification. Finally, applicability of cryogenic treatment for a range of ferrous alloys is presented with an emphasis on scope for future research.